Photoelectrochemical activity of magnetron sputtered ZnO thin films: role of thermal annealing. (16th July 2022) - Almamari, M.R.; Ahmed, N.M.; Holi, A.M.; Yam, F.K.; Al-Zahrani, A.A.; Almessiere, M.A.
In this paper, the effect of annealing temperature on the properties of ZnO thin films (ZOTFs) obtained using the well-known RF magnetron sputtering technique was investigated using their photoresponse in a photoelectrochemical cell. Properties pertaining to morphology, composition, structure, and optical were examined by field emission scanning electron microscopy (FESEM), energy-dispersive X-ray spectrometer (EDX), X-ray diffraction (XRD), and ultraviolet-visible spectroscopy (UV-vis), respectively. Results from FESEM showed that the surface of the ZOTFs nanoparticles was very compact, with grain size 63.32 nm at 400°C. When compared to other temperatures, 400°C contributes to a wide surface area resulting in a significantly enhanced PEC response. The ZOTF which was prepared under 400°C of annealing temperature, exhibited the highest photocurrent density 0.034 mA cm -2 and photoconversion efficiency (0.026%).